Addressing the Gap Between Academic Research and Grassroots Public Health Practice: Supporting Policy, Systems, and Environmental Changes in Rural Communities. Issue 1 (May 2023) - Gabbert, Kerry Darr; Tompkins, Nancy O'Hara; Murphy, Emily
Public health practice continues to expand beyond traditional partners to increase reach and impact in communities. This is particularly important in rural communities, who face inequities in the social determinants of health and increased chronic disease burden. However, the capacity for non-traditional community organizations to understand and implement public health work varies widely. Promoting policy, systems, and environmental change strategies (PSE's) is a promising method to support public health in rural communities, due to their variety, flexibility, and potential impact. Using a mixed methods approach to data analysis, we explore the barriers, challenges, and lessons learned from efforts in two rural Appalachian counties to stimulate use of PSE strategies through micro-funding. Several significant barriers were identified: challenges with evaluation and reporting, and lack of understanding and limited utilization of PSE strategies. Successful approaches to overcome these barriers included (1) changing reporting processes to reduce reliance on technology and shift reporting burden from community partners to researchers, (2) adapting data collection to capitalize on strengths of project partners, and (3) abandoning scientific language to embrace more common terminology used in communities. Policy changes were the least utilized strategy. This strategy may be less relevant in rural grassroots organizations with a small staff. Additional research into barriers to policy change is recommended. Enhanced training and support for grassroots, local-level PSE interventions could expand public health promotion in rural areas, reducing rural health disparities.